2018
DOI: 10.1084/jem.2016107002142018c
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Enzymatic lipid oxidation by eosinophils propagates coagulation, hemostasis, and thrombotic disease

Abstract: The authors regret that an error appeared in their original version of Fig. 4. Some of the PE and PS species listed on the x axis of Fig. 4 B were incorrect. The corrected figure and corresponding legend appear below.The online HTML and PDF versions of this paper have been corrected. The error remains only in the print version. -dependent externalization of aminophospholipids (APL) at the surface of eosinophils. OH indicates hydroxyl group. Data are representative of at least three independent experiments. Err… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Work by Moosbauer et al (35) showed that blood eosinophils produce and can release TF, which suggests that eosinophils play an upstream role in thrombin activation. Furthermore, eosinophils can generate thrombin in a TF-dependent manner when exposed to a procoagulant phospholipid surface enriched in 12/15 lipoxygenase-derived oxidized phospholipids (36).…”
Section: Discussionmentioning
confidence: 99%
“…Work by Moosbauer et al (35) showed that blood eosinophils produce and can release TF, which suggests that eosinophils play an upstream role in thrombin activation. Furthermore, eosinophils can generate thrombin in a TF-dependent manner when exposed to a procoagulant phospholipid surface enriched in 12/15 lipoxygenase-derived oxidized phospholipids (36).…”
Section: Discussionmentioning
confidence: 99%